How I solve: `4*log_a 6-3*log_a 5-4*log_a 2` =

### 1 Answer | Add Yours

The expression 4*log_a 6 -3log_a 5 - 4*log_a 2 has to be simplified.

Use the property a*log b = log b^a, log a+ log b = log(a*b) and log a - log b = log(a/b)

`4*log_a 6 -3log_a 5 - 4*log_a 2`

= `log_a 6^4 - log_a 5^3 - log_a 2^4`

= `log_a (6^4/(5^3*2^4))`

= `log_a (81/125)`

**The required result is **`log_a (81/125)`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes